مؤشرات المعرفة والرقمنة والمِنْهاج لضمان جودة التعليم العالي - كبوط,عبد الحليم (University of Eloued جامعة الوادي, 2023)
Abstract: We try to approach the topic of the relationship of knowledge, digitization, and the curriculum to the quality of higher education by defining it and identifying its indicators, foundations, steps, and mechanisms, while demonstrating its effectiveness and importance to ensure the quality of higher education in university institutions in the Arab world. The following problem was raised: Are the indicators of digitization (Artificial Intelligence), knowledge, and an effective curriculum reassuring and promising a future full of the quality of our higher education in our Arab world and our Islamic nation? Or are they indicators of disappointment and portend ambiguity, mediocrity and fading? What is the extent of the impact of these important indicators on the outputs of higher education and on the productivity and economics of Arab university knowledge? In order to answer this, the methodology followed in this articl requires dividing it into an introduction and three topics. The first of which is entitled Components of Knowledge, Artificial Intelligence (digitization), and Curriculum/Educational Program. The second topic is under the title of the foundations of training programs and curricula in Algeria and their drawbacks. As for the third topic, its title is a study of cultural criticism of formation and the future of the university and educational system, then followed by a conclusion containing the most important visions and ideas, the most important results of the research, some questions raised, and then some recommendations. أحاول في أسطر هذا المقال مقاربة موضوع علاقة المعرفة والرقمنة والمنهج بجودة التعليم العالي من خلال بيان تعريفها والتعرف على مؤشراتها وأسسها وخطواتها وآلياتها مع تبيين فعاليتها وأهميتها لضمان جودة التعليم العالي في المؤسسات الجامعية بالوطن العربي. ومنه طُرحت الإشكالية التالية: هل مؤشرات الرقمنة (الذكاء الاصطناعي) والمعرفة والمنهاج الفعال تبعث على الطمأنينة وتبشر بمستقبل حافل بجودة تعليمنا العالي في وطننا العربي وأمتنا الإسلامية؟ أم أنها مؤشرات تبعث على الخيبة وتنذر بالغموض والرداءة والتلاشي؟ وما مدى تأثير هذه المؤشرات الهامة على مُخْرَجات التعليم العالي وعلى إنتاجية واقتصادية المعرفة الجامعية العربية؟ وللإجابة على ذلك قُسِّم المقال إلى مقدمة وثلاثة مباحث؛ الأول منها: مقومات المعرفة والذكاء الاصطناعي (الرقمنة) والمنهاج/البرنامج التعليمي. والمبحث الثاني: أسس برامج ومناهج التكوين بالجزائر ومآخذهما. أما المبحث الثالث: دراسة نقد ثقافية للتكوين ومستقبل النظام الجامعي والتربوي، ثم خاتمة احتوت على أهم الرؤى والأفكار وأهم نتائج البحث وبعض الأسئلة المثارة ثم بعض التوصيات.
Keywords: الرقمنة; ضمان الجؤدة; Indicator; Knowledge; digitization; curriculum; quality assurance; education